Using science-based role-play simulations to inform payment for hydrological services program design in Mexico. Issue 139 (January 2023) - Urcuqui-Bustamante, Andres M.; Selfa, Theresa; Ashcraft, Catherine M.; Asbjornsen, Heidi; Jones, Kelly W.; Manson, Robert H.; Mayer, Alex
Abstract: Payments for hydrological services (PHS) apply an incentive-based approach to achieve conservation and socioeconomic goals. PHS policies are most successful when they are designed and implemented with participation from diverse stakeholders and respond to local needs and conditions. Role-play simulations (RPS) engage stakeholders from different organizations and decision-making roles in policy deliberations and innovations. This paper explores how a science-based RPS encourages participation from diverse actors to inform PHS policy innovation in Veracruz, Mexico. We present results from two RPS workshops which engaged 69 stakeholders in negotiations on the future design of a hypothetical PHS program. Our RPS integrated qualitative and quantitative information from operating PHS programs to inform a hypothetical, but realistic, decision-making scenario. This paper analyzes data collected from surveys of workshop participants, audio recordings of workshop discussions, and post-workshop, in-depth interviews. We found the RPS fostered collaborative decision-making by engaging participants in constructive conversations about PHS program design options to effectively contribute to forest conservation and socioeconomic well-being, including incentivizing environmentally friendly farm practices and complementing cash payment with in-kind transactions. We also found the collaborative method of RPS challenged the exclusive role of technical expertise in decision-making by eliciting ideas for improvement of PHS programs and fostering understanding and empathy towards others and their interests, particularly for small landowners who do not typically participate in decision-making. We conclude that a science-based RPS can be a valuable tool for encouraging multi-stakeholder participation in policy design that reflects local environmental and socio-economic values and needs. Highlights: Role-play simulation (RPS) is a method to engage stakeholders in policy deliberations and innovation. RPS promotes critical thinking about the design and approach of PHS policy. RPS can potentially inform PHS policies. RPS negotiations can contribute to mutual understanding between different stakeholders. RPS negotiations can be a valuable tool for encouraging multi-stakeholder participation in generating policy options.